PERFORMANCE OF REPRESENTATIVE UNIT HYDROGRAPH DERIVED FROM DIFFERENT NUMBER OF CASES - Sri Harto Br; Ika Tyasning Yudiyanti; Revianti Coenraad (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
Unit Hydrograph (UH) theory is known as the old theory applied in designing water works. This has been developed by Sherman 80 years ago, but up to now its merit is still studied all over the world. Even the last publication was found in the year 2009. There are some numbers of questions following its applications. One major problem is the number of cases used in deriving observed UH to obtain the representative unit hydrograph. Studies have been done in some catchments in Central Java and in Yogyakarta special territory, by comparing design discharge calculated with representative UH derived from several cases and the discharge obtained from frequency analysis. The result showed that representative UH derived from 10 cases or more give more or less constant deviation. Keywords: Unit Hydrograph, Representative Unit Hydrograph, Linearity.